RELATIONSHIP ANALYSIS AND CONCEPT OF HUMAN CAPITAL THEORY AND EDUCATION - rothomi, abday; Rafid, Muh (EDUCATUM: Scientific Journal of Education, 2023)
This study aims to describe and analyze the concept of Education and human capital and the relationship of human capital and education. The research method used is qualitative research with descriptive analysis techniques with library studies (library research). The results showed that the management of human capital can be done through the educational process with the aim as administrative requirements and as capital to increase productivity and performance. Because based on research that has been described previously the theory of human capital has an influence on the behavior of Indonesian people in education. Education is an investment of human capital in the form of time and cost that is seen as one of the most important forms of human capital investment (human capital), both for individuals and for organizations. The benefits obtained for the individual are in addition to knowledge, skills, and experience in an indeterminate time will provide work productivity and performance.